Natural-Resource Depletion, Habit Formation, and Sustainable Fiscal Policy : Lessons from Gabon - Olters, Jan-Peter (IMF Working Papers; Working Paper ;, 2006)
While models based on Friedman's (1957) permanent-income hypothesis can provide oilproducing countries with long-run fiscal targets, they usually abstract from short-run costs associated with consolidation. This paper proposes a model that takes such adjustment costs (or "habits") into account. Further operational realism is added by permitting differential interest rates on sovereign debt and financial assets. The approach is applied to Gabon, where oil reserves are expected to be exhausted in 30 years. The results suggest that Gabon's current fiscal-policy stance cannot be maintained, while the presence of habits justifies smoothing the bulk of the adjustment toward the sustainable level over three to five years.